Respon Pertumbuhan Dan Produksi Tanaman Bawang Merah (Allium ascalonicum L.) Dengan Pemberian Kompos Limbah Pisang Fhia-17 Dan Kompos Limbah Kandang Sapi - Fauzi Azhari; Suswati Febri; Ahmad Rafiqi (Universitas Medan Area, 2022)
Shallot (Allium ascalonicum L.) is one of the main vegetable in Indonesia and has many benefits. However, the production of shallots has not been stable in the past few years due to crop failures. Tree Caured by attacks by plant-disturbing that can reduce yields by 50%-75%. Banana waste has not been widely used for compost, while the potential for banana waste contains important. Manure compost is a provider of nutrients that are gradually renewed and available to plants. Soil fertilized with cow manure for a long time can still give good results. This research method used a factorial randomized block design consisting of 2 factors, namely 1). Banana Waste Compost FHIA-17 (P) consists of 4 levels, P0 = Control, P1 = 5 tons/ha, P2 = 10 tons/ha, P3 = 15 tons/ha. 2) Cowshed Compost (K) which consists of 4 levels, namely K0 = Control, K1 = 5 tons/ha, K2 = 10 tons/ha, K3 = 15 tons/ha. The results of this study showed that the application of FHIA-17 banana waste compost did not show a significant effect on the growth and production of shallot plants, and the application of cow manure compost did not show a significant effect on the growth and production of shallots.